Ambidextrous Leadership: Insights from a Comprehensive Systematic Review - Zain, Feri (Implementasi Manajemen & Kewirausahaan, 2024)
In an era of rapidly changing business and increasing complexity, leaders are faced with the challenge of managing uncertainty and competing in a dynamic environment. This research aims to explore what consequences will be experienced when organizations implement ambidextrous leadership based on existing literature. Therefore, we also want to identify avenues for future research to further develop and expand the literature related to ambidextrous leadership. This literature review included 40 articles from the first to 4th quartile in the Scopus database. This study finds that the antecedence of ambidextrous leadership is associated with several outcomes at individual, team, and organizational levels. This framework can help organizations identify the consequences of ambidextrous leadership.